Analysis of basketball offensive attachment and its relationship to successful correction of school teams participating in national school games - العيد بن سميشة (sports creativity, 2025)
The study aimed to identify the success rates of offensive booking and types of teams participating in the national games in basketball, as well as to identify the relationship between cases of successful arrest and successful correction of their results. The researcher used the descriptive method in the survey method to address the problem of research and achieve itsobjectives, (6) six teams, so the number of the sample (72).The results of the study showed a high percentage of the application of offensive booking in the sample teams, and the existence of a correlation between the offensive booking and successful correction of the results of the teams participating in the national games in basketball, and recommends the researcher to take care of exercises for offensive booking because of his important role in scoring points for the team.